The Role of Labor Market in Microeconomic Growth - Nababan, Mikhael Roy; Yudha Sinaga; Natasya Sembiring; Perbina Tarigan (ROE: Research of Economics and Business, 2025)
The labor market plays an important role in supporting microeconomic growth, especially for MSMEs that contribute significantly to GDP and job creation in Indonesia. However, labor market imbalances, such as high unemployment rates and skills mismatches, remain a challenge. This study uses a qualitative approach through literature review and secondary data analysis. The research findings show that the labor market contributes to equal labor distribution, increased productivity, and job creation. However, MSMEs face obstacles such as limited capital, limited access to technology, and complex regulations. Support from communities such as Local Preneur Indonesia, along with synergy between the government and the private sector through microcredit programs, digitalization, and regulatory simplification, can strengthen the MSME ecosystem. With the right strategy, MSMEs can grow more competitively and make a significant contribution to microeconomic development